Graphene–DNAzyme junctions: a platform for direct metal ion detection with ultrahigh sensitivity. Issue 4 (19th February 2015) - Gao, Li; Li, Le-Le; Wang, Xiaolong; Wu, Peiwen; Cao, Yang; Liang, Bo; Li, Xin; Lin, Yuanwei; Lu, Yi; Guo, Xuefeng
Abstract : We describe a method of creating graphene–DNAzyme junctions capable of directly detecting paramagnetic Cu 2+ with femtomolar sensitivity and high selectivity. Abstract : Many metal ions are present in biology and in the human body in trace amounts. Despite numerous efforts, metal sensors with ultrahigh sensitivity (<a few picomolar) are rarely achieved. Here, we describe a platform method that integrates a Cu 2+ -dependent DNAzyme into graphene–molecule junctions and its application for direct detection of paramagnetic Cu 2+ with femtomolar sensitivity and high selectivity. Since DNAzymes specific for other metal ions can be obtained through in vitro selection, the method demonstrated here can be applied to the detection of a broad range of other metal ions.